Comparing changes over time for two phenomena - Miłek, Michał (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
Statistical analyses in economics are often based on explaining the phenomena by comparing time series. The purpose of such types of analyses is to find out the similarity and schematic behavior of phenomena which appear in the data. Usual time series are compared with the use of a different similarity measure which, in accordance with the literature, could be divided into four categories. In this article, I propose a method that allows to indicate whether two time series are generated by the same stochastic processes. For this purpose, I analyze a method based on a permutation test. The idea of this test is much simpler than the tests based on theoretical distributions. I also conducted a simulation analysis based on the data generated according to different scenarios, subsequently comparing the results of that analysis.
Mathematical Economics, 2015, Nr 11 (18), s. 89-98
Keywords: time series comparing; permutation test; distance measure